INTERNET OF THINGS EMPOWERED BY ARTIFICIAL INTELLIGENCE OF THINGS - Askarbek Aslan (Research Retrieval and Academic Letters, 2025)
This paper explored the two technologies that create intelligently connected systems - Internet of Things (IoT) and Artificial Intelligence of Things (AIoT). The Internet of Things combined with the most dynamic technology of artificial intelligence (AI) is expected to make the Internet of Things system smarter and easily imitate human activity. However, what modern challenges await such synergy and what ways of their development can be expected? This paper aims to study the development prospects of both Internet of Things (IoT) and Artificial Intelligence of Things (AIoT).